Survey on Topics related to Traditional Medicine in Modern Medical Education - Seyyed Mahmoud Hosseini-Ashlaghi; Saeid Saffarian Hamedani; Omme Kolsoum Gholamhosseinzadeh; Hasan Siamian (Mashhad University of Medical Sciences, 2022)
Background: Traditional medicine has been formally accepted in the country for many years, but it has an indefinite place in the modern medicine curriculum. While it exists in the modern medical curriculum; however, the extent of its use in this program is not clear. Therefore, the purpose of this study was to study the level of attention to issues related to traditional medicine in the curriculum of modern medical education at Mazandaran University of Medical Sciences from the students' perspectives.Methods: This descriptive-analytical study was conducted using a researcher-made questionnaire among 297 medical students of Mazandaran Medical School as a statistical sample. Data were analyzed using one-sample t-test.Results: 59% of the total respondents were women,  57% of whom were married and 44% of them were residents. According to students, the use of 'lifestyle adjustment' (essential set) and 'traditional medicines' in the modern medical education curriculum of students as well as the use of 'preventive methods' of traditional medicine in modern medical education are moderate. The use of traditional medicine treatment methods in medical education in the students' curriculum is insignificant.Conclusion: Results showed that the concepts of traditional medicine as complementary medicine were included in the modern medical education curriculum to a moderate extent. But it is not formally defined in the curriculum but is provided to students in the form of history or side information. This study suggests that the concepts of traditional medicine should be formally included in the curriculum of modern medical education, and the importance and value of years of experience in this science should be provided to modern physicians.